Green Light Reader : Daniel's Mystery Egg - Ada, Alma Flor; Karas, G. Brian (San Diego, 2000)
When he finds an egg, Daniel and his friends try to guess what is inside.
"Level 2 grades 1-2"--cover.
Keywords: Eggs; Fiction; Early readers